2019
DOI: 10.1097/hs9.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid‐Derived Suppressor Cells in Hematologic Diseases: Promising Biomarkers and Treatment Targets

Abstract: Myeloid-derived suppressor cells (MDSC) are a heterogeneous group of immature myeloid cells that exist at very low numbers in healthy subjects but can expand significantly in malignant, infectious, and chronic inflammatory diseases. These cells are characterized as early-MDSCs, monocytic-MDSCs, and polymorphonuclear-MDSCs and can be studied on the basis of their immunophenotypic characteristics and their functional properties to suppress T-cell activation and proliferation. MDSCs have emerged as important cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 101 publications
(297 reference statements)
0
50
0
Order By: Relevance
“…As summarized in Table 3 , a variety of immune cells contribute to the pathogenesis of hMDS, including cytotoxic T cells, regulatory T cells, natural killer cells, B-cells, monocytic cells, mesenchymal stem cells, and mastocytes [ 18 , 19 , 20 , 21 ]. Additional findings include the development of paroxysmal nocturnal hemoglobinuria (PNH) clones and the positivity of autoimmunity tests.…”
Section: Pathogenesismentioning
confidence: 99%
“…As summarized in Table 3 , a variety of immune cells contribute to the pathogenesis of hMDS, including cytotoxic T cells, regulatory T cells, natural killer cells, B-cells, monocytic cells, mesenchymal stem cells, and mastocytes [ 18 , 19 , 20 , 21 ]. Additional findings include the development of paroxysmal nocturnal hemoglobinuria (PNH) clones and the positivity of autoimmunity tests.…”
Section: Pathogenesismentioning
confidence: 99%
“…In humans, MDSCs have been related to worse outcomes in hematological malignancies (60,61); therefore, MDSCs were suspected to be involved in relapses after allo-HSCT. However, in the allo-HSCT setting, only a few prospective studies have reported a significantly higher probability of relapse in patients with higher M-MDSC frequencies than other patients, in the 30 days following allo-HSCT (52,53).…”
Section: Impact Of Mdscs On the Gvt Effectmentioning
confidence: 99%
“…suppressing host immune responses [6][7][8]32 . The phenotypic marker of immature myeloid cells (CD33 + HLA-DR −/low ) is a characteristic feature of human suppressive MDSCs, which are further categorized into monocytic MDSCs (M-MDSCs) and granulocytic MDSCs (G-MDSCs) based on the differential expression of the CD14 and CD15 markers, respectively 33,34 . We have recently reported an expansion of M-MDSCs, which inhibited T cell functions via promoting regulatory T cell (Treg) differentiation during chronic viral infections [13][14][15][16] .…”
Section: Mdscs Expand During Chronic Hcv Infection Mdscs Play a Critmentioning
confidence: 99%